Ludartin treatment exhibits promising inhibitory effect on the epithelial ovarian cancer growth and metastasis (Bangladesh Journal of Pharmacology, 2016)
In the present study, the effect of ludartin on OVCAR5 ovarian carcinoma cells was investigated. MTT cell assay was used for the analysis of cell viability and wound healing assay for migration potential. Results revealed that ludartin treatment at 10 and 30 µM doses reduced the cell viability from 94 to 38%. The invasive potential was decreased from 62 to 24% with increase in ludartin concentration from 10 to 30 µM. Western blot analysis showed that ludartin treatment reduced the expression of p-FAK in OVCAR5 cells significantly. Ludartin treatment for 48 hours also caused a significant decrease in the expression of MMP-2 and MMP-9 in OVCAR5 cells at a concentration of 30 µM. The metastatic regions were absent in the rats treated with 30 µM/kg doses of ludartin daily for 15 days.  Thus, ludartin treatment inhibits the proliferation, invasion and migration of ovarian cancer cells through down-regulation of pFAK and MMPs, therefore can be used for the treatment of ovarian cancer.Video Clip of Methodology:Cell proliferation assay: 2 min 45 sec   Click to watch